Efektivitas Intervensi Keperawatan Komunitas dalam Menurunkan Stres Remaja di Provinsi Aceh - Dedi Irawan (Media Ilmiah Kesehatan Indonesia, 2026)
Stress among adolescents has become an increasingly important public health issue, particularly due to academic pressure, social demands, and limited access to mental health services. This study aimed to examine the effectiveness of a community nursing intervention in reducing stress levels among adolescents in Aceh Province. This study employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. A total of 60 respondents were selected through purposive sampling and divided into an intervention group (n = 30) and a control group (n = 30). Stress levels were measured using the validated Depression Anxiety Stress Scale (DASS-42). The intervention was delivered as a structured program consisting of psychoeducation, group-based stress management, and peer support over six sessions. The Paired t-test showed a significant reduction in stress scores in the intervention group, from 26.43 to 16.15 (p < 0.001). The Independent t-test also showed a significant difference between the intervention and control groups after the intervention (p < 0.05). These findings indicate that the community nursing intervention was effective in improving coping ability and reducing stress among adolescents. The integration of community-based programs is needed as a preventive strategy to support adolescent mental health.